EFFECTIVENESS OF MEDICAL PLAY IN REDUCING ANXIETY AND PAIN IN HOSPITALIZED PEDIATRIC PATIENTS: A SYSTEMATIC REVIEW - Sri Rosma Kencana; Dessie Wanda; Ayu Widya (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Introduction : Children who are sick are sometimes required to undergo a hospitalization process which can make children feel uncomfortable and traumatized. Hospitalization is a negative experience that can make children experience anxiety and pain. During the hospitalization process, medical procedures are often carried out, especially invasive procedures for installing peripheral intravenous access which will cause pain and anxiety. Medical play is a distraction technique to deal with anxiety and pain. Purpose : The purpose of this study is to see the effect of medical play on anxiety and pain in children. Methods : A systematic review was conducted after searching the electronic databases Science Direct, Scopus, EBSCOhost, Pubmed, and hand searching (1984–2022) for a total of nine articles. Search using the following keywords anxiety, child, hospitalized, medical play, and pain. Results : The search results showed that seven of the nine reviewed articles showed that medical play was beneficial in reducing anxiety and pain in children, while two more articles stated that children's responses were better when given music therapy than medical play. Conclusion : Medical play is widely practiced in the Americas, Europe and Australia and is effective in reducing anxiety and pain in children